Sistem Pendukung Keputusan dengan Metode AHP dalam Penentuan Pemilihan Minat Siswa - Wenni Afrodita; Sarjon Defit; Yuhandri Yuhandri (JUKI : Jurnal Komputer dan Informatika, 2023)
Senior High School is a level of formal education in selecting student interests selection of specialization is a grouping of learning interests that makes it easier for students to pursue knowledge in further education, especially in tertiary institutions. Specialization is designed to guide students so they can follow certain subjects at the next school level. Decision Support System has many methods that can be used. One of the methods used in this research is the Analytical Hierarchy Process (AHP) method. This decision support model will break down complex multi-factor or multi-criteria problems into a hierarchy, so that the decisions taken can be more objective. Because the concept of the AHP method is to change qualitative values into quantitative values. The Decision Support System uses the Analytical Hierarchy Process method to determine student interest choices in selecting interest in major subjects. This is a decision support system created to determine interest selection for class X students at SMAN 1 Kinali. The specialization that will be selected is taken from various criteria such as the average value of report cards, understanding of the material and students' interests. Test results on the AHP method obtained an accuracy of 90% from 10 test data. With this application, students are expected to get specialization according to their respective interests and abilities.)